2023
DOI: 10.3390/biology12040536
|View full text |Cite
|
Sign up to set email alerts
|

Tackling Inequalities in Oral Health: Bone Augmentation in Dental Surgery through the 3D Printing of Poly(ε-caprolactone) Combined with 20% Tricalcium Phosphate

Abstract: The concept of personalized medicine and overcoming healthcare inequalities have become extremely popular in recent decades. Polymers can support cost reductions, the simplicity of customized printing processes, and possible future wide-scale expansion. Polymers with β-tricalcium phosphate (TCP) are well known for their synergy with oral tissues and their ability to induce osteoconductivity. However, poor information exists concerning their properties after the printing process and whether they can maintain an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…The dimensions of the test specimen for biological assays featured a thickness of 1 mm, while the diameter adhered to the standard dimensions of wells in multiwell plates, namely 11.5 mm in diameter. Consistent with our earlier research on PCL + 20% β-TCP [23], PLLA + 10% HA (synthetic hydroxyapatite) and PCL + 20% β-TCP were 3D-printed using a Prusa Mini LCD ® 3D printer (Prusa Research a.s., Prague, Czech Republic), featuring a 0.2 mm nozzle size and printing temperatures of 175 • C or 110 • C, respectively. No additional post-printing procedures were conducted.…”
Section: Sample Design and 3d Printingsupporting
confidence: 83%
See 3 more Smart Citations
“…The dimensions of the test specimen for biological assays featured a thickness of 1 mm, while the diameter adhered to the standard dimensions of wells in multiwell plates, namely 11.5 mm in diameter. Consistent with our earlier research on PCL + 20% β-TCP [23], PLLA + 10% HA (synthetic hydroxyapatite) and PCL + 20% β-TCP were 3D-printed using a Prusa Mini LCD ® 3D printer (Prusa Research a.s., Prague, Czech Republic), featuring a 0.2 mm nozzle size and printing temperatures of 175 • C or 110 • C, respectively. No additional post-printing procedures were conducted.…”
Section: Sample Design and 3d Printingsupporting
confidence: 83%
“…These findings underscore the impact of even a modest proportion of HA in modifying the material's mechanical characteristics. Conversely, in our prior analysis of PCL + 20% β-TCP [23], the composite exhibited statistically negligible alterations in behavior compared to pure PCL, registering values of 0.3-0.4 GPa and 13-15 MPa. It is worth noting that the PCL + 20% β-TCP composite underwent ISO 14937-200935 sterilization using a 2% peracetic acid solution without significant changes [23], in accordance with Italian national law n.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Therefore, the aim for future research and clinical studies should address the use of the largely available material, such as resorbable biopolymers, that can be easily printed by the Fused Deposition Modeling technique (FDM) [ 17 ]. In the mentioned study, the authors showed the capacity of ceramic biopolymers in terms of cell proliferation and maturation, which is one of the most important milestones for medical grade classification.…”
mentioning
confidence: 99%